Criminal & Civil Liability Related to Misuse of Illegal Fintech Customer Data During The Covid-19 Pandemic - Hendrik Wijaya; Herwastoeti Herwastoeti (Universitas Muhammadiyah Malang, 2022)
The covid-19 outbreak that swept across the world has caused a crisis in the economic sector, where physical distancing policies affect the world of trade and tourism. The bankruptcy of companies, hotels, and small and medium-sized micro-enterprises resulted in massive job cuts. Therefore, many people lose their livelihoods and borrow money to meet their daily needs. Financial technology is an advancement of the times in the industrial era 4.0, as a form of convenience in financial services of tempted communities and applying for loans to financial technology. However, instead of getting a financial solution, what happens is the opposite. Where the public is even entangled in the existence of illegal financial technology and there is a misuse of their personal data. It is true that there is an agreement that allows the debtor to access the personal data of the creditor, but whether with it immediately the debtor can misuse the customer's personal data. Therefore, in this study, the author is interested in reviewing how criminal and civil liability related to the emergence of illegal financial technology agreements during the Covid-19 pandemic. The research methods used are normative juridical with statute approach and comparative approach, as well as qualitatively described legal material analysis. The result obtained is, illegal fintech e-agreements do not meet the subjective and objective requirements of the agreement and are related to the misuse of customer data, which can be held criminally accountable are fintech law bodies and debt collectors.